Grace Padaca's rhetoric of the 2004 gubernatorial race a dramaturgical analysis - Latosa, Augustus Ceasar Destura (2011)
Grace Padaca of Isabela gained national and international prominence when she defeated Faustino Dy, Jr. in the 2004 gubernatorial race. The researcher believed that Padaca's rhetoric became a potent tool in her victory. Therefore, the researcher sought to answer five research questions: 1. What dramatic events catapulted Grace Padaca to the governorship? 2. Do Padaca's rhetorical acts reflect moral courage and altruism? If so, How? 3. How did Padaca's audiences respond to the messages of her rhetorical acts or public performances? 4. How did Padaca's rhetoric impact her audiences in the gubernatorial drama? 5. What significance(s) can be drawn from her rhetoric? In this research, Padaca was the primary respondent while representatives from different sectoral groups were the secondary respondents. The researcher used Campbell and Burkholder's rhetorical criticism framework to analyze Padaca's rhetoric. In particular, he chose dramaturgy as the select critical perspective to analyze Padaca's rhetorical performances. This research presents the following findings: 1. When Padaca accepted the challenge to run for governor, she received enormous support from different stakeholders who shared with her idealism. She countered black propaganda devised her opponent with rhetoric. 2. Padaca's rhetorical acts manifested moral courage and altruism when she decided to take on the challenge despite the risks because of her desire to liberate Isabela. 3. Padaca's audiences respond to the messages of her rhetorical acts by supporting her in the campaign and giving her the 44,000-lead margin over Dy. 4. Padaca's rhetoric empowered her audiences by making them her co-liberators who could harness their potentials in a free Isabela society. 5. Padaca's rhetoric was artistically significant because of (1) the consistency of her thoughts to liberate Isabela with her persuasive messages of freedom and (2) the three personae she displayed one, a potential leader who empowered her audiences by persuading them to vote of their own volition; two, a political leader who used rhetoric to respond to black propaganda; three, an individual who was transformed from and indecisive citizen to a morally courageous and altruistic leader. Moreover, Padaca's rhetoric was ethically significant because it embodied hope for transformational leadership and may serve as rhetorical benchmark that poses a challenge to Padaca herself, political neophytes, and experienced politicians to fuse action with words. This research concludes with matrix of contradictions of the sociopolitical drama in order to show the tensions that built up before, during, and after the gubernatorial drama. The researcher recommends the use of dramaturgy to analyze social action in other fields and the use of Padaca's rhetoric in public communication classes. The researcher further recommends advocacy groups to encourage primncipled and high-quality women to run for public office.